The 2012 economic contribution of Colorado's wine industry: the role of consumers, wineries, and tourism - Thilmany, Dawn, author; Costanigro, Marco, author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 2013)
The Colorado Wine Industry Development Board commissioned a research project in 2012–2013 to assess the economic contributions the Colorado wine industry makes to the state. Conducted by Colorado State University, the research builds upon a similar 2005 study to better measure the wine industry's growth in Colorado over the past several years.
Role of consumers, wineries, and tourism
November 2013
Professor Dawn Thilmany Ph.D., from CSU's Department of Agricultural and Resource Economics (DARE) oversaw the study with support from Associate Professor Marco Costanigro, Ph.D., and others.
Keywords: Wine industry -- Economic aspects -- Colorado; Tourism -- Colorado